2019
DOI: 10.1016/j.jneuroim.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of neurotransmitters and neurochemicals with lymphocytes

Abstract: Neurotransmitters and neurochemicals can act on lymphocytes by binding to receptors expressed by lymphocytes. This review describes lymphocyte expression of receptors for a selection of neurotransmitters and neurochemicals, the anatomical locations where lymphocytes can interact with neurotransmitters, and the effects of the neurotransmitters on lymphocyte function. Implications for health and disease are also discussed. As defined above, a neurotransmitter must be produced by neurons. Lymphocytes can be expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 328 publications
(388 reference statements)
0
47
0
10
Order By: Relevance
“…For example, failure of intact SNS signaling impairs the steady-state circadian rhythmicity of hematopoietic stem cells and disturbs their mobilization [123]. Basic βadrenoreceptor (β-AR) activity is programmed to retain lymphocytes within the lymph nodes, while activation of β-AR results in a rapid decline in lymphocytes in peripheral blood and lymphatic fluid by blocking efficient emigration [96,124]. Further studies provided evidence that activation of β-AR in T cells promotes interactions between β-AR and C-C motif chemokine receptor (CCR)7 and CCR4 [96].…”
Section: Sympathetic Nervous Systemmentioning
confidence: 99%
“…For example, failure of intact SNS signaling impairs the steady-state circadian rhythmicity of hematopoietic stem cells and disturbs their mobilization [123]. Basic βadrenoreceptor (β-AR) activity is programmed to retain lymphocytes within the lymph nodes, while activation of β-AR results in a rapid decline in lymphocytes in peripheral blood and lymphatic fluid by blocking efficient emigration [96,124]. Further studies provided evidence that activation of β-AR in T cells promotes interactions between β-AR and C-C motif chemokine receptor (CCR)7 and CCR4 [96].…”
Section: Sympathetic Nervous Systemmentioning
confidence: 99%
“…In our previous study, we have seen the expression of muscarinic acetylcholine receptor (subtype M2) on lymphocytes and DCs in mouse Peyers' patches 33 . Some other studies also showed that neurotransmitters such as acetylcholine and dopamine regulated the functions of B/T cells and DC/macrophages 34,35 . Some neurotransmitters are immunosuppressive, while others may stimulate and activate immunity 35,36 .…”
Section: Discussionmentioning
confidence: 97%
“…Some other studies also showed that neurotransmitters such as acetylcholine and dopamine regulated the functions of B/T cells and DC/macrophages 34,35 . Some neurotransmitters are immunosuppressive, while others may stimulate and activate immunity 35,36 . Thirdly, inflammatory mediators such as pro-inflammatory cytokines, prostaglandins, serotonin, and histamine from immune cells (even from neural cells or glial cells) can have variable effects on nerves of PNS 37,38 .…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, neurons and immune cells share a broad collection of surface receptors, secretory molecules, and signal transducers 82 . In particular, many neurotransmitters/neuropeptides and their synthesis/degradation machineries traditionally considered speci c for neurons are expressed in immune cells, although their functions in the immune system are to a large extent still unknown 83,84 . Studying these molecules and their regulatory mechanisms may provide new perspectives in tumour immunology and identifying new drug targets for cancer immunotherapies, as exempli ed by our current nding of this "MAO-A-ROS axis" regulation of TAM polarization in the TME.…”
Section: Discussionmentioning
confidence: 99%